Ändamålsanpassad TINA-sortering av sågtimmer - Sjölander, Henrik (SLU/Dept. of Forest Products, 2003)
Swedish sawmills of today suffer from unsatisfying economy with high costs and low benefits. The economical result depends on how well the sawmill can use their raw material. Iggesund Timber AB, a sawmill in the Holmen group, produces a large amount is enduse orientated products for the woodworking industry. Therefore the aim of this student thesis was to investigate the possibility of automatic enduse orientated quality grading of Scots Pine (Pinus sylvestris) saw logs by using a gamma-ray log scanner.